Strategy for Optimizing The Management of Library Circulation Services - Br Sembiring, Agnes Wemona; Samosir, Fransiska Timoria; Sa'diyah, Lailatus (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
This research examines the management of circulation services in the Diplomatic Library of the Ministry of Foreign Affairs. The diplomacy library is a special library under the auspices of the Indonesian Ministry of Foreign Affairs. Circulation service management is useful for improving circulation services. This research aims to analyze whether circulation service management in diplomatic libraries is running well or not. This research uses qualitative methods with observation, interviews and documentation. This research involved interviews with librarians and users. The results of the research show that the management of circulation services in diplomatic libraries has been carried out as effectively as possible but there are still things that need to be improved so that the use of circulation services increases.Good management of circulation services will indirectly introduce diplomatic libraries and effective use of circulation services proves that management of diplomatic libraries is running well